Wayang sebagai Media Persuasif aldam Menanamkan Nilai-Nilai Islam Ditinjau dari Perspektif Psikologi - Nurdahlia, Dwi Ulfa (Proceedings of Annual Conference for Muslim Scholars, 2024)
This study aims to analyze wayang as a persuasive medium in inculcating Islamic values, viewed from a psychological perspective. Wayang, as a traditional performing art, has great potential to convey moral and ethical messages aligned with Islamic teachings, such as tolerance, justice, and compassion. Through a literature review research method, this study analyzes various academic sources from a psychological perspective related to wayang, and its impact on individual attitudes and behaviors. The results of the study show that wayang performances can influence individuals' perceptions and actions, encouraging them to apply Islamic values in their daily lives. In addition, the emotional impact generated by the performances also contributes to the formation of a harmonious social identity. This study affirms that wayang is not only entertainment but also an effective educational tool in inculcating positive values and Islamic teachings in society.